Chemical engineering around the 5, 12-dihydroindolo[3, 2-a]carbazole scaffold: Fine tuning of the optical properties of visible light photoinitiators of polymerization. (5th June 2022) - Hammoud, Fatima; Hijazi, Akram; Ibrahim-Ouali, Malika; Lalevée, Jacques; Dumur, Frédéric
Graphical abstract: Highlights: Carbazole derivatives have been examined as photoinitiators of polymerization. Polymerization processes in the visible range have been initiated. Carbazoles exhibit interesting photophysical properties. Polymerization of various monomers was possible under low light intensity. Abstract: 5, 12-Dihydroindolo[3, 2- a ]carbazole is a promising scaffold for the design of visible light photoinitiators of polymerization due to the simultaneous presence of two carbazole moieties that can be differently functionalized. Notably, redshift of the absorption spectra can be facilely obtained by nitration of one of the two carbazoles, the second carbazole group being functionalized with various groups. Dinitration of 5, 12-dihydroindolo[3, 2- a ]carbazole is another efficient approach for designing dyes with strong absorptions extending over the visible range. In this work, a series of 36 compounds never reported in the literature and differing by the substitution pattern have been designed and synthesized. Notably, the possibility to design push–pull dyes by Knoevenagel and Claisen Schmidt reactions, to introduce electroactive groups such as thiophene by Suzuki cross-coupling reactions or to design water soluble chromophore has been explored. To evidence the interest of these structures, photopolymerization experiments have been carried out at 405 nm and the polymerization of acrylates has been examined in thick and thin films. To support the polymerization efficiency, mechanisms involved in the free radical polymerization of acrylates have been established by the combination of various techniques including UV–visible absorption and fluorescence spectroscopy, cyclic voltammetry and photolysis experiments.